An Empirical Study of the Relationship Between Social Networking Sites and Students' Engagement in Higher Education. (September 2019) - Koranteng, Felix N.; Wiafe, Isaac; Kuada, Eric
This article investigates how students' online social networking relationships affect knowledge sharing and how the intensity of knowledge sharing enhances students' engagement. It adopts the social capital theory as the basis for investigation, and the partial least square structural equation modeling was used to examine the hypothesized model. Responses from 586 students in higher education were analyzed. The findings provided empirical evidence which contradicts the argument that students perceive social networking sites as an effective tool for learning. Also, contrary to previous studies which posit that knowledge sharing impacts engagement, it was observed that there is no relationship between the two. However, as social networking sites differ in terms of member behavior norms, it is envisaged that if a similar study is conducted and limited to a specific academically inclined social networking site such as Academia.edu, ResearchGate, Mendeley, and so on, different findings may be observed.